Teknik Pemeriksaan MRI Genu Dengan Penambahan Sequence Axial 3D Spoiled Gradient Recalled Echo - Rafa Zenitha Azzahra; I Made Lana Prasetya; Intan Lesmanasari (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2023)
Magnetic Resonance Imaging (MRI) is a medical diagnostic imaging technique that works on the principle of nuclear magnetic resonance. MRI aircraft can produce diagnostic images of the inside of the human body in both sagittal, coronal, and transverse cuts, Magnetic resonance imaging (MRI) is a widely accepted non-invasive technique for the evaluation of cartilage lesions. The femur, tibia, fibula, and patella are united into one complex group by ligaments. According to Moeller, Genu Examination uses STIR Sequence, Sagital T2 Weighted Fat saturated, Sagittal 3D GRE, Proton Density weighted fat saturated T1 Coronal. The author's purpose in conducting this study is because Genu Examination at one of the Jakarta Hospital in the Case of Soft Tissue Tumor, Meniscus Tear and Oesteoarthritis added the Axial 3D SPGR sequence. The research method used is descriptive research with an observational approach. Data collection was carried out on June 5 to August 31 using Mri GE aircraft with a power of 1.5 Tesla. The patient samples used in this study were three patients with clinical Soft Tissue Tumor, Meniscus Tear, and Osteoarthritis. Data collection was carried out through observation, interviews and Genu Examination Documentation with the addition of Axial 3D SPGR. The examination is carried out using Quad Knee Coil, the patient's position is supine, feet first. The sequences used in the examination at one of the Jakarta hospitals are Axial Proton Density Fat saturated, Sagital Proton Density Fat saturated, Sagital T2, Coronal Proton Density Fat saturated, Coronal STIR. The role of the Axial 3D SPGR sequence is to evaluate articular cartilage due to its clear depiction of cartilage morphology and high signal to noise ratio (SNR) images.